# Simplify the expressions and find the value if x is equal to 2

(i) x + 7 + 4 (x – 5) (ii) 3 (x + 2) + 5x – 7

(iii) 6x + 5 (x – 2) (iv) 4(2x – 1) + 3x + 11

**Solution:**

According to the question, the value of 'x' is given as 2.

Let us substitute the value of 'x' in the following expressions.

(i) x + 7 + 4(x - 5)

= x + 7 + 4x - 20

= 5x -13

Now putting the value of x = 2 in 5x -13

= (5 × 2) - 13

= 10 - 13

= -3 is the required value.

(ii) 3(x + 2) + 5x- 7

= 3x + 6 + 5x - 7

= 8x - 1

Now putting the value of x = 2 in 8x - 1

= (8 × 2) -1

= 16 -1

= 15 is the required value.

(iii) 6x + 5(x - 2)

= 6x + 5x - 10

= 11x - 10

Now putting value of x = 2 in 11x - 10

= (11 × 2) - 10

= 12 is the required value.

(iv) 4(2x -1) + 3x +11

= 8x - 4 + 3x +11

= 11x + 7

Now putting value of x = 2 in 11x + 7

= (11 × 2 ) + 7

= 22 + 7

= 29 is the required value.

**Video Solution:**

## Simplify the expressions and find the value if x is equal to 2 (i) x + 7 + 4 (x – 5) (ii) 3 (x + 2) + 5x – 7 (iii) 6x + 5 (x – 2) (iv) 4(2x – 1) + 3x + 11

### Maths NCERT Solutions Class 7 - Chapter 12 Exercise 12.3 Question 6

**Summary:**

The expressions are simplified with the value of x equal to 2. (i) x + 7 + 4(x - 5) = -3 (ii) 3(x + 2) + 5x - 7 = 15 (iii) 6x + 5(x - 2) = 12 (iv) 4(2x - 1) + 3x + 11 = 29